2015
DOI: 10.1177/1077559515602095
|View full text |Cite
|
Sign up to set email alerts
|

Self-Criticism as a Mechanism Linking Childhood Maltreatment and Maternal Efficacy Beliefs in Low-Income Mothers With and Without Depression

Abstract: The primary aim of the current study was to examine self-criticism as a potential mechanism mediating the relation between mothers' own childhood maltreatment history and changes in subsequent maternal efficacy beliefs in a diverse sample of low-income mothers with and without Major depressive disorder (MDD). Longitudinal data were drawn from a larger randomized clinical trial evaluating the effectiveness of interpersonal psychotherapy (IPT) for depression among low-income mothers and their 12-month old infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 88 publications
(104 reference statements)
1
20
0
Order By: Relevance
“…This jeopardizes how mothers adaptively appraise the goals and content of their interactions, the psychological resources they need to respond to them, and positive attributions to family members' intentions and behaviors (Dix and Meunier, 2009). Disturbances in this process are empirically associated with lower perceived maternal competence (Michl et al, 2015). The dysfunctional appraisal processing of depressed mothers might also reduce cooperative coparenting and undermining coparenting by promoting negative evaluations of the other parent and negative attributions to other parent behaviors, as suggested by previous empirical work (Jia and Schoppe-Sullivan, 2011).…”
Section: Depressive-somatic Symptoms Parenting and Coparentingmentioning
confidence: 90%
“…This jeopardizes how mothers adaptively appraise the goals and content of their interactions, the psychological resources they need to respond to them, and positive attributions to family members' intentions and behaviors (Dix and Meunier, 2009). Disturbances in this process are empirically associated with lower perceived maternal competence (Michl et al, 2015). The dysfunctional appraisal processing of depressed mothers might also reduce cooperative coparenting and undermining coparenting by promoting negative evaluations of the other parent and negative attributions to other parent behaviors, as suggested by previous empirical work (Jia and Schoppe-Sullivan, 2011).…”
Section: Depressive-somatic Symptoms Parenting and Coparentingmentioning
confidence: 90%
“…This risk factor may be particularly salient for parents who have experienced maltreatment in childhood, especially in the context of challenging child behavior (e.g. Michl et al , 2015 ; Kunseler et al , 2016 ). Conversely, positive parenting self-evaluations may represent an important intervention target and protective factor that buffers parents from the cumulative impact of environmental adversity ( Peterson et al , 2003 ; Fisher et al , 2016 ) and difficulties that emerge during the transition to parenthood ( Mihelic et al , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…the extent to which a parent evaluates themselves as competent in their parenting role) are associated with aspects of parent well-being, parenting behavior and child development (for reviews see Coleman and Karraker, 1997 ; Jones and Prinz, 2005 ). For example, parents with low parenting self-efficacy are more likely to be depressed ( Kohlhoff and Barnett, 2013 ; Michl et al , 2015 ) and less likely to report satisfaction with parenting ( Coleman and Karraker, 2000 ). In contrast, robust associations have been reported between endorsements of high parenting self-efficacy and developmentally supportive parenting behavior ( Bohlin and Hagekull, 1987 ; Teti and Gelfand, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, parental efficacy beliefs, or the degree to which parents perceive themselves as able to master the varied tasks associated with parenting a child, have emerged as a strong, direct predictor of positive parenting practices (Ardelt & Eccles, 2001; Izzo, Weiss, Shanahan, & Rodriguez-Brown, 2000). Importantly, research has identified a link between higher levels of maternal depression and lower levels of maternal parenting efficacy (Jones & Prinz, 2005; Kohlhoff & Barnett, 2013; Michl, Handley, Rogosch, Cicchetti & Toth, 2015). Taken together, it is evident that depressed mothers are vulnerable to maladaptive parenting beliefs and behaviors, both of which heighten risk among offspring.…”
Section: Maternal Depression Attachment Quality and Parentingmentioning
confidence: 99%